Toxocariasis: an underdiagnosed cause of parasitic prurigo. - Paquet, Ph.; Laso-Dosal, F.J.; de la Brassinne, M. (European Journal of Pediatric Dermatology, 2018)
Toxocariasis is a parasitic disease characterized by the presence in humans of larvae of the genus Toxocara. Toxocara canis (T. canis), the common nematode worm of the dog, appears to be the primary causative agent in temperate climates. The cat round worm, Toxocara canis, is also potentially able to produce toxocariasis in man (10). The resulting general and dermatological clinical picture is common and non-specific, which leads to considerable underdiagnosis.